Performing Artists between Chile and Costa Rica in the Seventies: (Up)rooting, Art and Politics - Castro, Anabelle Contreras (2021)
This book comprises a collection of dialogues with Performing Artists, main characters of a forced displacement from Chile to Costa Rica. This forced displacement was caused by Augusto Pinochet’s violent seizure of power in 1973.The female authors of the book aim to propose a series of analyses focused on the impact that fact had on the socio-political, economic and cultural field from both nations.